2003
DOI: 10.1152/jn.01143.2002
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of Remote Cortical Regions After Ischemic Brain Injury: A Potential Substrate for Stroke Recovery

Abstract: Although recent neurological research has shed light on the brain's mechanisms of self-repair after stroke, the role that intact tissue plays in recovery is still obscure. To explore these mechanisms further, we used microelectrode stimulation techniques to examine functional remodeling in cerebral cortex after an ischemic infarct in the hand representation of primary motor cortex in five adult squirrel monkeys. Hand preference and the motor skill of both hands were assessed periodically on a pellet retrieval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
282
3
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 401 publications
(302 citation statements)
references
References 58 publications
(62 reference statements)
14
282
3
3
Order By: Relevance
“…Other work using electrophysiological techniques also finds that peri-infarct tissue moves relative to the infarct location. (Eysel and Schweigart, 1999;Frost et al, 2003;Jenkins and Merzenich, 1987;Reinecke et al, 2003;Schiene et al, 1999;Zepeda et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other work using electrophysiological techniques also finds that peri-infarct tissue moves relative to the infarct location. (Eysel and Schweigart, 1999;Frost et al, 2003;Jenkins and Merzenich, 1987;Reinecke et al, 2003;Schiene et al, 1999;Zepeda et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, intracortical microstimulation and fMRI studies have found that electrophysiological maps can reorganize after cortical stroke in order to compensate for the functional loss in the stroke infarct. Better behavioural outcome is also correlated with the extent of cortical map reorganization (Castro-Alamancos and Borrel, 1995;Friel et al, 2000;Frost et al, 2003;Gharbawie et al, 2005;Kleim et al, 2003;. This cortical reorganization may be mediated by two mechanisms.…”
Section: Electrophysiological Changesmentioning
confidence: 99%
See 2 more Smart Citations
“…This region neighbouring the cortical infarct likely represents an active brain region involved in post-stroke plasticity with suggested positive effects on functional improvement 158,159 .…”
Section: Commentsmentioning
confidence: 99%